THE INFLUENCE OF IMPLEMENTATION ALTERNATIVE AUDIT PROCEDURES ON THE AUDIT QUALITY RESULTS IN THE COVID-19 PANDEMIC: (Study at Auditors on Public Accounting Firm Auditors in Central Java) - Dewi Saptantinah Puji Astuti; Khofifah Indar Pratama; Djoko Kristianto (Transpublika Publisher, 2022)
The accuracy of the audit results is determined by the auditor's ability to perform their duties in accordance with the applicable public accountant code of ethics and auditing standards. The auditor can find irregularities in the client's accounting system while auditing the financial statements of the client and report them in the audited financial statements. The purpose of this study was to determine whether the covid-19 pandemic that occurred affected auditors in auditing the financial statements of a company, causing differences in the quality of audit results. This study uses a survey method using a quantitative approach. The data collection method used a questionnaire with a sample of 90 respondents who were both junior and senior auditors at the Public Accounting Firm in Central Java. Sampling technique with saturated sampling. Based on the results, all variables have a significant effect on the quality of audit results during the COVID-19 pandemic. This shows that if the variables of audit evidence, audit digitization, and professional skepticism are good, the quality of the audit results will also be good.